The Influence of Parental Holding with Sitting Position on The Successful Installation of Intravenous Fluid Drips in Childhood Patients in The Emergency Installation of Toto Kabila Hospital - Suleman, Ibrahim; Jamal Bahua; Sumiyati Moo (International Journal of Public Health Excellence (IJPHE), 2023)
IVFD installation is one of the most common procedures given to children, especially in hospitals. Around 80% of pediatric patients receive an infusion procedure which causes the child to experience unpleasant experiences such as hospitalization problems. So that there is no adverse response for the child and during treatment therapy is needed to reduce distress and suppress this negative response. One of them is Parental Holding or the holding position carried out by parents or family. The research method used in this research is quantitative research, namely experimental research with a quasi-experimental approach. Quasi experimental research design with a Two Group Post test only Design approach. The sampling technique used is Accidental Sampling. The number of respondents was 60 people consisting of 30 respondents in each group. Implementation of Parental Holding with Sitting Position is carried out every time an IVFD is installed on a pediatric patient until completion. Analysis in this study used the Wilcoxon and Mann Whitney U tests with α ≤ 0.05. The results of this study using the Mann Whitney U statistical test showed that there was an effect of Parental Holding with Sitting Position on the Success of IVFD Installation in Pediatric Patients in the Emergency Room, p=0.047, (p value ≤ 0.05). It is suggested that the results of this research can be used to maximize nursing services, especially in independent nursing actions by implementing the Holding Parental with Sitting Position when installing IVFD on pediatric patients, so that in the future this nursing action can become a standard operational procedure that applies in hospitals.